2008
DOI: 10.1016/j.immuni.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Association of the T Cell Receptor with CD8 Reverses Anergy in Human Tumor-Infiltrating Lymphocytes

Abstract: For several days after antigenic stimulation, human cytolytic T lymphocyte (CTL) clones exhibit a decrease in their effector activity and in their binding to human leukocyte antigen (HLA)-peptide tetramers. We observed that, when in this state, CTLs lose the colocalization of the T cell receptor (TCR) and CD8. Effector function and TCR-CD8 colocalization were restored with galectin disaccharide ligands, suggesting that the binding of TCR to galectin plays a role in the distancing of TCR from CD8. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
177
0
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(185 citation statements)
references
References 58 publications
(73 reference statements)
5
177
0
3
Order By: Relevance
“…Alternatively, it has been proposed that CD8 molecules interact with pMHC in two distinct orientations, potentially explaining why memory cells, as opposed to naïve cells, were insensitive to anti-CD8 blockage (35). Several studies indicate a unique role for CD8 in fine-tuning the activation threshold of T cells (36,37) and in compensating for lower numbers of antigenspecific pMHC complexes (38). Our study supports the importance of CD8 accessibility during primary responses of naïve CD8 + T cells.…”
Section: Discussionsupporting
confidence: 80%
“…Alternatively, it has been proposed that CD8 molecules interact with pMHC in two distinct orientations, potentially explaining why memory cells, as opposed to naïve cells, were insensitive to anti-CD8 blockage (35). Several studies indicate a unique role for CD8 in fine-tuning the activation threshold of T cells (36,37) and in compensating for lower numbers of antigenspecific pMHC complexes (38). Our study supports the importance of CD8 accessibility during primary responses of naïve CD8 + T cells.…”
Section: Discussionsupporting
confidence: 80%
“…The levels of IFN-γ production by NY-ESO-1-reactive CD8 + T cells in ovarian cancer TILs are relatively high and correlated with tetramer fluorescence intensity. Although the link between reduced tetramer fluorescence intensity and effector function may reflect failure of TCR and CD8 colocalization on CD8 + TILs, leading to inability to produce IFN-γ in response to stimulation (19), it does not fully account for the functional heterogeneity of tumor-infiltrating antigen-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two problems at the bases of this difficulty can be identified in the low frequency and low affinity of CD4 1 T cells [7,8]. Furthermore, the activation state of CD4 1 T cells determines the staining ability of MHC class II tetramers [12,15] unlike CD8 1 T-cell staining by MHC class I tetramers [43], making more difficult the detection ex vivo of quiescent CD4 1 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two problems at the bases of this difficulty can be identified in the low frequency and low affinity of CD4 1 T cells [7,8]. Furthermore, the activation state of CD4 1 T cells determines the staining ability of MHC class II tetramers [12,15] unlike CD8 1 T-cell staining by MHC class I tetramers [43], making more difficult the detection ex vivo of quiescent CD4 1 T cells.In the present study, we have identified a new critical parameter for the functionality of MHC class II tetramers, namely the binding of peptides in a single register in the groove of MHC class II molecules, required for the generation of homogenous peptide-MHC conformers endowed with optimal avidity for their cognate TCR.The relevance of this parameter has become evident in the analysis of human CD4 1 T-cell responses specific for the MAGE-A3 tumor antigen utilizing promiscuous helper peptides, that is to say peptides that can bind a wide range of HLA-DR alleles or contain more than one epitope [30,31]. The HLA class II -restricted peptides derived from MAGE-A3 were selected using the predictive algorithm Tepitope [32] for being highly promiscuous, to be suitable for vaccination protocols and immunomonitoring in cancer patients irrespective of their HLA-DR typing.…”
mentioning
confidence: 99%